Hydroformylation over polyoxometalates supported single-atom Rh catalysts - Feng Shixiang; Yu Qi; Ma Xinbin; Yu Xiaohu; Yan Ning (National Science Open)
Atomic dispersion of Rh on phosphotungstic acid (PTA) salts was achieved by a self-assembled precipitation method using alkali metal ions as coprecipitation reagents. During styrene hydroformylation, the supported Rh single-atom catalyst (Rh1/M-PTA, M refers to an alkali metal ion) demonstrated an optimum turnover frequency (TOF) of 1076 h−1. With increasing ionic radius, the pore size of the catalysts increased in the following order: Rh1/K-PTA<Rh1/Rb-PTA<Rh1/Cs-PTA. The catalytic activity showed the same trend, suggesting a positive correlation between pore size and hydroformylation performance. Further experimental data suggested that temperature is an important factor affecting not only the activity but also the selectivity. This study enriches the understanding of the structure and catalytic properties of PTA-supported single-atom materials. The cation-controlled synthesis of catalysts may also be applied to prepare other single-atom catalysts with tunable pore size distributions.